1982
DOI: 10.1111/j.1365-246x.1982.tb04945.x
|View full text |Cite
|
Sign up to set email alerts
|

B-polarization induction in two generalized thin sheets at the surface of a conducting half-space

Abstract: A new closed-form solution is obtained analytically for a Bpolarization induction problem of geophysical interest, in which a local region of the Earth is represented by a generalized thin sheet at the surface of and in electrical contact with a uniformly conducting half-space. The generalized sheet, first introduced by Ranganayaki & Madden, is a mathematical idealization of a double layer which consists, in this problem, of two adjacent half-planes with distinct conductances representing a surface conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…However, Dawson et al (1982) obtained an exact analytical solution for this double layer problem in the B-polarisation mode, and showed that the exponential decay of the anomalous field on either side of a conductivity discontinuity in the top sheet (for this analysis the lower sheet must have the same characteristics on both sides of the discontinuity) is governed by the attenuation constants -Im (v~) and -Im (v~), where v? = ao~l,~z7 a'h,~z/a2 (16) This above defined 'adjustment distance', 6a, is obviously correct only for a 2D model.…”
Section: Adjustment Distancementioning
confidence: 98%
“…However, Dawson et al (1982) obtained an exact analytical solution for this double layer problem in the B-polarisation mode, and showed that the exponential decay of the anomalous field on either side of a conductivity discontinuity in the top sheet (for this analysis the lower sheet must have the same characteristics on both sides of the discontinuity) is governed by the attenuation constants -Im (v~) and -Im (v~), where v? = ao~l,~z7 a'h,~z/a2 (16) This above defined 'adjustment distance', 6a, is obviously correct only for a 2D model.…”
Section: Adjustment Distancementioning
confidence: 98%
“…However, as discussed by Ranganayaki and Madden (1980), Dawson et al (1982), and Jones (1983), the appropriate scale length is given by the adjustment distance, not the skin depth, and at low frequencies this distance can be many hundreds of kilometers. As formulated by Ranganayaki and Madden (1980) and Dawson et al (1982), this distance applies on the ocean side of the coastline, so it cannot be directly applied as there is no conducting upper thin sheet on the land side. Nevertheless, the induction arrows clearly indicate that there is an observable effect.…”
Section: Induction Vectorsmentioning
confidence: 99%
“…A number of 2‐D algorithms produce consistent results. What is also important is that the 2‐D algorithms can be tested using analytical solutions found by Weidelt (1971) for E ‐polarization, and by Dawson et al (1982) and Dawson (1996) for B ‐polarization. The 2‐D code used in our test was developed by Poll (1994) and based on the scheme by Brewitt‐Taylor & Weaver (1976) and Weaver & Brewitt‐Taylor (1978).…”
Section: Test Of the Thin‐layer Algorithmmentioning
confidence: 99%
“…Generalized thin‐sheet models have successfully been used by Dawson et al (1982), Berdichevsky & Zhdanov (1984), Weaver & Dawson (1992), Weaver (1994), and other authors. We believe that the opportunities offered by this class of models are far from exhausted.…”
Section: Introductionmentioning
confidence: 99%